Development of Urban Community Through Creative Business Groups Towards Independent Village in Menteng Village Jekan Raya District Palangka Raya City - Hasanah, Noor; Fitriyah, Ries Dyah (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
The purpose of this research is to find a strategy in developing Creative Business Groups in Menteng Village, precisely in the RT 05/RW XII environment and its surroundings. The group's efforts have been to recycle used tires into useful items, for example making flower pots and others, focusing on the environmental theme. Furthermore, mentoring is carried out because the group understands that they have potential in the field of business for the development of their group. They mobilize the community to join together in managing the business and its environment in collaboration with stakeholders (RT). The strategy used is to analyze pentagonal assets and determine asset advantages using the Orid Technique, which is then described in the program strategy analysis table (related to program potential, expectations, and plans). The summary of the agreed program is to strengthen group management and design development efforts for infrastructure development before the business is realized. The Asset Based Community-Driven Development (ABCD) approach is used as the method of this action research, namely community development carried out based on the assets owned, namely human, social, and supportive environmental assets. Community development process with independent participation (self-mobilization) through Appreciative Inquiry. The discovery of data is covered in the FGD process, interviews, observation and documentation, and the evaluation techniques used are before-after and historical plots. Program changes can be analyzed by looking at the development of a more structured group management and realizing the development of a business development plan. So that if the business starts operating, in the future it can have an impact on strengthening the economy, social and environment of the community.